The role of parents in child feeding - Esquiavan , Adriana da Silva; Santos , Adelcio Machado (Seven Editora, 2023)
The practice of healthy habits regarding food ranges from counseling, educational processes, support, and motivation by parents. The study aims to identify the role of parents in infant feeding. Food is the fundamental tool for the proper development and maintenance of the human body. Building healthy eating habits is assertive to avoid irreversible damage to health, and parents’ habits tend to be copied by children in their daily practices. Most parents have difficulty identifying eating problems in their family members. The bad eating habits acquired in childhood will be repeated in adulthood. Given this situation, it is necessary to have more efforts by our managers, with the implementation of educational programs aimed at the family and school, through public policies, or expansion of intersectoral actions that have a positive impact on the determinants of health and nutrition. DOI: https://doi.org/10.56238/devopinterscie-058